Diplomasi Kopi Indonesia di Kancah Dunia - Sophiana Widiastutie; Chusnu Syarifa Diah Kusuma; Ari Pradhanawati; Mustofa Agung Sardjono (Indonesian Perspective, 2022)
Indonesia is one of the fourth largest producers and exporters of coffee beans in the world. Coffee can be used to promote Indonesian culture abroad as well as to increase the potential of coffee in supporting the nation's economy. This approach is called Coffee Diplomacy, which is a gastrodiplomacy approach by utilizing coffee in the form of beverage dishes. Coffee diplomacy is a new tool for Indonesian soft power diplomacy to strengthen Indonesia's bilateral and multilateral relations with other countries, carried out by not limited state actor, but also non-state actors including individuals. This shows the ability of Indonesian coffee as an instrument of cultural and economic diplomacy. The culture of coffee beverages in various regions in Indonesia is closely related to the culture of tolerance in Indonesian society. In the context of international relations, Indonesian coffee diplomacy is a nation branding effort aimed at building a positive image of Indonesian culture, while creating opportunities for economic cooperation to improve the welfare of the Indonesian people.